2001
DOI: 10.1002/ccd.1175
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ultrasound‐detected cerebral microemboli in patients undergoing cardiac catheterization using an in vitro middle cerebral artery model

Abstract: Cerebral embolization has been documented as one of the complications of diagnostic heart catheterization by transcranial Doppler (TCD). This study aimed to evaluate our hypothesis that the nature of embolic signals involved in different stages of catheter manipulation may be distinct. TCD-detected cerebral emboli occurring at different phases of cardiac catheterization were registered and differentiated by comparing their acoustic signatures with the Doppler signals generated from clinically frequently encoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In a small series of patients, routine coronary angiography did not affect CK MB isoforms 18 . Transcranial Doppler studies have suggested that embolic signals may be recorded during the various phases of cardiac catherization 16 …”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In a small series of patients, routine coronary angiography did not affect CK MB isoforms 18 . Transcranial Doppler studies have suggested that embolic signals may be recorded during the various phases of cardiac catherization 16 …”
Section: Discussionmentioning
confidence: 84%
“…Although previous reports have shown that embolization may occur during coronary angiography, 15–17 to our knowledge, this is the first prospective study to systematically address the issue of coronary embolization resulting in subtle myonecrosis during diagnostic coronary angiography. In a short report on 12 cases, Kettunen 17 had detected CK MB elevation in two patients, but this was attributed to preexisting subendocardial injury.…”
Section: Discussionmentioning
confidence: 93%
“…22 Vascular risk factors predominate in patients with postprocedure strokes, possibly contributing to atherosclerosis of the great vessels, a potential source of embolism. Furthermore, transcranial Doppler studies 33,34 have demonstrated high rates of microembolic signals. A recent prospective study 27 found higher rates of solid microemboli in patients with acute strokes that were apparent on MRI.…”
Section: Possible Originsmentioning
confidence: 99%